A Design of Hybrid CSMA using Sequential-based Scheduling Algorithm - Kim, Tae Yoon; Capon, Lara Fernandez; Park, Hyuk; Kim, Jae Hyun (International Conference on ICT Convergence, 2021)
Carrier sense multiple access (CSMA), a representative contention-based MAC protocol, plays an important role in a wireless communication system that requires efficient channel utilization. In particular, it can allocate channels dynamically because each node competes to get channels every period in the dynamic network environment, unlike the contention-free MAC protocol, which allocates channels statically. However, CSMA has performance degradation because as the number of nodes increases, the collision probability also increases. In this paper, we propose a hybrid CSMA using a sequential-based scheduling algorithm. Our proposed MAC protocol operates in two stages. The AP sends the node's sequence number and an ACK to the node that acquired the channel in the initial stage. Next, in the second stage, nodes transmit their data without collision using their assigned sequential number. Performance results show that the average throughput and the average delay are improved compared to conventional CSMA.
Keywords: Channel utilization; Contention-based; Contention-free; Efficient channels; Hybrid; Hybrid carriers; MAC; Mac protocols; Sequential-based; Wireless communication system; contention-based; contention-free; CSMA; hybrid; MAC; sequential-based